The Effect of the Concept Map Method on Student Learning Motivation in Geography Class XI Social Studies 3 in Public High School 8 Banjarmasin - Monalisa Monalisa; Deasy Arisanty; Herry Porda Nugroho Putro; Karunia Puji Hastuti; Bambang Subiyakto (Universitas Lambung Mangkurat, 2023)
Disaster mitigation material has many concepts that are prone to misconceptions and fragments. Mind maps are considered capable of providing a good understanding of concepts. This study aims to determine the application of the concept map learning method in natural disaster mitigation material to increase the motivation to learn the geography of grade XI Social Studies 3 students at SMA Negeri 8 Banjarmasin in the even semester of the 2022/2023 academic year. This is a class action research (PTK) carried out in 3 cycles. Each Cycle consists of stages of planning, execution of actions, observation, evaluation, and reflection. The study subjects were 35 grade XI Social Studies 3 students—data collection using four aspects of learning motivation questionnaires and five questions of learning outcomes tests. The results showed that the initial score of students' motivation to learn geography was 26% in Cycle I to 78.67% of motivated students, in Cycle II to 87.49%, and in Cycle III to 93.07% of students. The initial score of geography learning outcomes was 46% of students completed Cycle I, 77.14% of students completed Cycle II, 88.57% of students, and Cycle III, 94.29% of students. Based on the study's results, there was an increase in students' motivation to learn geography while applying the mind map method in disaster mitigation material. Preparing concept maps by students with the freedom to draw lines creates an independent and fun learning atmosphere. Mind maps provide an integrated understanding of the relationship between concepts in disaster mitigation materials.